Sharks and rays at Pelabuhan Perikanan Samudera (PPS) Lampulo, Banda Aceh, Indonesia: Morphometric characteristics and differentiators based on multivariate analysis - Hikmah, Nur; Nufus, Hayatun; Syahrial, Syahrial; Ezraneti, Riri; Astuti, Rika (Universitas Malikussaleh, 2024)
Tropical marine environments are abundant and diverse; therefore, shark and ray research at fishing port PPS Lampulo, Banda Aceh City was carried out focusing on morphometric characteristics and differences based on multivariate analysis in July 2020 to identify sharks and rays that landed at fishing port PPS Lampulo, Banda Aceh City and determine their primary characteristics. The shark and ray samples used were from the Indian Ocean and the Malacca Strait and measured total length (TL), fork length (FL), and standard length (SL) for sharks and disc width (DW), TL, and disc length (DL) for rays. Principal component analysis (PCA) and discriminant analysis (DA) were performed on the morphometric data. The PCA analysis revealed that sharks and rays caught in Pelabuhan Perikanan Samudera (PPS) Lampulo, Banda Aceh City, can be divided into two distinct groups. The first group of sharks consists of species with large FL and SL morphometrics, namely P. kamoharai, C. plumbeus, P. glauca, and A. superciliosus. The second group of sharks consists of species with large TL morphometrics, specifically A. pelagicus and C. plumbeus. For the ray group, the first group comprises species with large TL and DW morphometrics, represented by A. ocellatus. The second group of rays consists of species with large DL morphometrics, namely P. sephen and H. jenkinsii. The results of DA revealed distinct differences in the size of sharks caught in the Indian Ocean and the Strait of Malacca, specifically in PPS Lampulo, Banda Aceh City. However, no significant differences in size were observed for the rays, regardless of whether their size was measured using DW, TL, or DL.